COMMUNICATION - ORGANIZATIONS’ WORK DEVICE - LAVINIA HULEA (Annals of the University of Petrosani: Economics, 2010)
Communication represents a complex process of transmitting messages, owing to which the emitter encodes the information transmitted through a specific channel towards a receiver that will decode it. Owing to communication, organizations transmit to their customers the fact that they are capable of meeting one of their needs, of settling a problem or of offering a profit. Non-verbal and para-verbal communications usually accompany verbal communication. The importance of assimilating the forms of communication is, at an organizational level, a complex device that determines the mastering of certain techniques, procedures, and algorithms of encoding and decoding intricate messages transmitted through various channels.